Effect of fungicides in controlling root rot (Fusarium Solani) of chickpea - Morshed, M. G.; Kashem, M. A.; Hossain, I.; Yusop, Mohd Rafii; Abdul Latif, Mohammad (Marsland Press, 2014)
A field experiment was conducted in the field of Bangladesh Institute of Nuclear Agency sub-station, Ishurdi to determine the effect of different fungicides in controlling root rot of chickpea. Germination of chickpea were increased by treating seeds with secure 600WG (48.62%) followed by provax 200WP (44.38%) over control. Pre-emergence death of chickpea decreased up to 30.42% by treating seeds with secure 600WG over control. The lowest disease incidence (8.68%) was found in secure. Secure 600WG treating seeds decreased disease incidence 70.05% followed by Bavistin 68.57% over control. Seed treated with Secure 600WG and Bavistin increased plant stand by 28.56% and 27.97%, respectively over control. Maximum shoot length (11.78%) was found when seeds were treated with Secure 600WG, while maximum root length (21.80%) was recorded when seeds were treated with Provex 200WP over control. Seeds treated with Secure 600WG, Provex 200WP and Bavistin increased vigour index up to 66.94%, 63.28% and 56.68% over control. Seed treated with Secure 600WG resulted highest fresh weight of biomass (3031) which was 82.32% higher over control. Seeds treated with Secure 600WG also resulted highest grain yield (192.1g/m2) which was 81.50% higher over control.